PENGARUH PENGGUNAAN MEDIA AUDIO TERHADAP KETERAMPILAN MENYIMAK SISWA SEKOLAH DASAR - Triyawan, Deni; Khalidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to find out the audio media used to listen to folklore in class V of South Matan Hilir 02 Elementary School. The research method used is pre-experimental designs. The sample of this study was the fifth grade students totaling 19 people. The results of data analysis, get the posttest average in the experimental class of 69.444. The results of calculating data size size effect student learning outcomes experimental class obtained by 0.445 with the classification in the medium category, which means the use of audio media gives influence to the listening skills of children's stories in class V Public Elementary School 02 Matan Hilir Selatan Keywords: Audio Media, Listening Skills